Nutritional fulfillment for anaemia prevention in female adolescents: Perceived benefits, barriers and commitment - Mira Triharini; Ni Ketut Alit Armini; Retnayu Pradanie (Journal of the Pakistan Medical Association, 2024)
Objective: To identify the correlation of preventive nutrition for anaemia with perceived benefits, perceived barriers and commitment among young females. Method: The correlational, cross-sectional study was conducted from June to July 2022 in Surabaya, East Java, Indonesia, and comprised young females. The independent variables were perceived benefits, perceived barriers, and commitment. The dependent variable was preventive nutrition for anaemia. Data was collected online using Google Form. Data was analysed using a software SPSS version 23 Results: There were 112 females with mean age 19.63±1.501 years. There were 101(90.2%) aged 18-24 years, and 100(89.3%) were in senior high school. Perceived benefits (p=0.021; r=0.218), perceived barriers (p=0.002; r=-0.286) and commitment (p=0.000; r=0.345) had a significant relationship with preventive nutrition for anaemia. Conclusion: Perceived benefits and high commitment to increase preventive nutrition against anaemia was seen in female adolescents. However, high perceived barrier could suppress their preventive nutrition. Keywords: Adolescent behaviour, Anaemia, Diet, Health promotion, Nutritional status.